High rates of ineligibility for participation in trials of new therapies in non-alcoholic steatohepatitis: a systematic review. Issue 8 (August 2020) - Roskilly, Anna; Shearer, Jessica; Parker, Richard; Rowe, Ian A.
Abstract : Background and aims: Non-alcoholic fatty liver disease is common and there are a number of treatments in development. Patients with non-alcoholic steatohepatitis (NASH) and significant fibrosis are thought to be the population most in need of treatment. Identification of this group requires liver biopsy. The aim of this study was to identify the proportion of patients screened for phase 2 randomised controlled trials who subsequently entered these studies. Methods: Large, multicentre, phase 2 randomised controlled trials of pharmacological therapies for NASH were identified by systematic review. The pooled proportion of potential participants who entered the trials was estimated by meta-analysis. The reasons for trial ineligibility were separately extracted and analysed. Results: Thirteen reports of 14 trials were included. Overall, there were 4014 screened individuals included in the quantitative analyses and 53% were subsequently enrolled in a trial. Considering trials in which the entry criteria matched the current paradigm for treatment, that is, the presence of NASH and significant fibrosis, only 35% of screened individuals were eligible for trial entry. More than half of ineligible individuals were excluded on the basis of liver histology most often due to insufficient disease activity with or without insufficient fibrosis. Conclusion: The majority of patients considered at risk of NASH and fibrosis sufficient for treatment in randomised controlled trials are ineligible for trial entry. Most often, this is due to ineligible liver histology. These findings have implications for the design of future trials in NASH and for the applicability of treatments after licensing. Abstract : Supplemental Digital Content is available in the text.